Effect of magnetic field on precipitation kinetics and shear strength of Sn58Bi-Ni solders - Chuan-jiang Wu; Liang Zhang; Yu-hao Chen; Xin-quan Yu; Quan-Bin Lu; Wei-min Long (Materials & Design)
Magnetic-field-assisted soldering offered a promising approach for achieving high-reliability interconnects in space applications. In this study, Sn58Bi solder and its composites doped with 0.6 wt% Ni nanoparticles (NPs) or microparticles (MPs) were investigated to elucidate the effects of magnetic fields on the behavior of magnetic solders, with particular focus on microstructural evolution, grain orientation, and mechanical performance. The classical lamellar eutectic structure was transformed into a honeycomb-like morphology under the applied magnetic field, accompanied by an increased dislocation density. Meanwhile, the magnetic field suppressed Ni particle agglomeration and promoted the precipitation of fine (Cu, Ni)6Sn5 grains between the Sn and Bi phases, which produced a pinning effect. It also inhibited intermetallic compounds (IMC) layer growth, refined the IMC grains, and preserved their orientation. Consequently, the shear strength of joints soldered under the magnetic field increased by approximately 30 %. For the first time, first-principles calculations revealed how the synergistic effect of magnetic Ni doping and magnetic field application improved the mechanical and electronic properties of (Cu, Ni)6Sn5 IMC. These findings provided essential insights into the microstructural evolution of Sn-based magnetic solders under magnetic fields and contributed to the development of magnetic field-assisted soldering and the design of magnetic solder materials.